PERHITUNGAN PREMI BULANAN ASURANSI DANA PENSIUN MENGGUNAKAN METODE AGGREGATE COST PADA ASURANSI JIWA SEUMUR HIDUP - MIA NUR FATAYATIN; I NYOMAN WIDANA; DESAK PUTU EKA NILAKUSMAWATI (Mathematics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2025)
Pension insurance is a long-term financial program managed by an official institution. The premium, as the participant’s mandatory contribution, is determined by the type of product and the annuity chosen. Monthly premiums in a pension program play an important role in ensuring that participants receive benefits once they reach retirement age. This study aims to explain how monthly premiums are calculated using the Aggregate Cost Method in pension insurance programs. This method is chosen because it takes into account the participant’s average salary during their working years. The calculation is carried out by estimating all future benefit payments, which are then discounted using an assumed interest rate and survival probabilities based on mortality assumptions. The research uses data from employees who started working at the ages of 22, 25, and 30, in order to show how the entry age affects the amount of monthly premiums. The results indicate that both the monthly premium and the retirement benefits vary depending on the age at which the participant begins contributing. The earlier a person starts paying premiums, the lighter the financial burden they carry.